Selection of New Probiotics for Endometrial Health - Chenoll, Empar; Moreno, Inmaculada; Sánchez, María; Garcia-Grau, Iolanda; Silva, Ángela; González-Monfort, Marta; Genovés, Salvador; Vilella, Felipe; Seco-Durban, Cristina; Simón, Carlos; Ramón, Daniel (Frontiers in Cellular and Infection Microbiology, 2019)
Microbiota is a crucial player in gynecologic health, in which bacteria can shift to a dysbiotic state triggering a pathogenic process. Based on an ecological understanding of the problem, the aim of this study is to select a potential probiotic strain to improve female reproductive tract based on its capacity to initially lower pH and to promote the reduction of pathogenic bacteria. Based on this rationale, strain Lactobacillus rhamnosus BPL005 was initially selected for its capacity to reduce in vitro pH levels and produce organic acids. Subsequently, strain L. rhamnosus BPL005 (CECT 8800) was demonstrated to have a protective role on endometrial infections in an in vitro model of bacterial colonization of primary endometrial epithelial cells with Atopobium vaginae, Gardnerella vaginalis, Propionibacterium acnes and Streptococcus agalactiae. In this model, BPL005 when co-cultured with those pathogens was shown to lower pH and to produce organic acids, being lactic acid the most relevant. The co-cultivation of strain L. rhamnosus BPL005 with tested reference pathogens produced a significant reduction in P. acnes and St. agalactiae levels and a non-significant reduction in A. vaginae and G. vaginalis. The colonization of L. rhamnosus BPL005 in the culture decreased IL-6, IL-8 and MCP-1, heightened in the presence of pathogens, and increased IL-1RA and IL-1 beta. Finally, safety was evaluated showing no signs of cytotoxicity, irritation in vaginal tests or allergic contact dermatitis potential through the Local Lymph Node Assay. Overall, these results show the potential of L. rhamnosus BPL005 strain as a probiotic in gynecological health.